plzz explain me.... why alpha² + beta² = (alpha + beta )² - 2alpha²+beta²
(for convenient, the question was If alpha and beta are the zeroes of the polynomial ax + bx + c.
then find alpha⁴+ beta⁴ ? )
Attachments:
![](https://hi-static.z-dn.net/files/d8c/e988a354a3007c7d71e3ea12712f1829.jpg)
Answers
Answered by
11
Let us take alpha as A and beta as B.
As we know ,
( A + B )² = A² + B² + 2AB
( A + B )² - 2AB = A² + B²
so ,
( alpha + beta )² - 2 alpha . beta = alpha ² + beta²
As we know ,
( A + B )² = A² + B² + 2AB
( A + B )² - 2AB = A² + B²
so ,
( alpha + beta )² - 2 alpha . beta = alpha ² + beta²
sunny640:
A²+B²=( A+B )² - 2AB plzz explain
Answered by
5
Answer:
Step-by-step explanation: (alpha+ Beta)^2 = apha^2 + beta^2 + 2alpha beta
Now if we subtract 2alphabeta from (alpha + beta )^2 we get alpha^2 + beta^2
Hope it will help us
Please mark me as brainliest
Similar questions